2015
DOI: 10.1038/bjc.2015.361
|View full text |Cite
|
Sign up to set email alerts
|

Serum lactate dehydrogenase and survival following cancer diagnosis

Abstract: Background:There is evidence that high level of serum lactate dehydrogenase (LDH) is associated with poorer overall survival in several malignancies, but its link to cancer-specific survival is unclear.Methods:A total of 7895 individuals diagnosed with cancer between 1986 and 1999 were selected for this study. Multivariable Cox proportional hazards regression was used to assess overall and cancer-specific death by the z-score and clinical categories of serum LDH prospectively collected within 3 years before di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 48 publications
2
65
0
1
Order By: Relevance
“…LDHA and B are responsible for encoding the M and H subunits of LDH and the high Ldha / Ldhb expression ratio observed in high-grade TRAMP tumors leads to the production of a predominance of the LDH5 isoenzyme (5M subunits) favoring increased lactate production. In patient studies, a high serum LDH level is associated with aggressive disease and a poor survival for a variety of cancers (24,25) including prostate cancer (26), and inhibition of the LDH catalyzed production of lactate has become a therapeutic target (27,28). Studies using patient biopsies and prostate tissue slices removed at surgery have demonstrated increased steady state pools of lactate, HP 13 C-lactate production, increased LDH activity, and increased mRNA expression of LDHA and MCT1 and 4 in prostate cancer tissues similar to what has been observed in the TRAMP model used in this study (29).…”
Section: Discussionmentioning
confidence: 99%
“…LDHA and B are responsible for encoding the M and H subunits of LDH and the high Ldha / Ldhb expression ratio observed in high-grade TRAMP tumors leads to the production of a predominance of the LDH5 isoenzyme (5M subunits) favoring increased lactate production. In patient studies, a high serum LDH level is associated with aggressive disease and a poor survival for a variety of cancers (24,25) including prostate cancer (26), and inhibition of the LDH catalyzed production of lactate has become a therapeutic target (27,28). Studies using patient biopsies and prostate tissue slices removed at surgery have demonstrated increased steady state pools of lactate, HP 13 C-lactate production, increased LDH activity, and increased mRNA expression of LDHA and MCT1 and 4 in prostate cancer tissues similar to what has been observed in the TRAMP model used in this study (29).…”
Section: Discussionmentioning
confidence: 99%
“…Koehler et al65 detected an association between abnormal GGT values and mortality in older people. Wulaningsih et al66 and Liu et al67 found that increased serum LDH values predicted mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Az emelkedett LDH a teljes és a daganatspecifikus túlélés független prognosztikai faktorának bizonyult (HR 1,43 [95%-os CI 1,31-1,56], és HR 1,46 [95%-os CI 1,32-1,61]) [100].…”
Section: A Kiindulási Szérum-ldh éS a Rosszindulatú Daganatos Betegekunclassified